Impact of control on the efficiency of direct purchases in the registration area n° XIII - Tacna headquarters. 2016 - Copa Colque, Freddy Silverio (2020)
The objective of the research is to determine the effect of the level of control on the efficiency of direct purchases in the Registration Zone No. XIII - Tacna Headquarters. 2016. It is affirmed that the level of control has a significant impact on the efficiency of direct purchases in the Registration Zone No. XIII - Sede Tacna, 2016. The research was developed under a quantitative approach, non-experimental or "ex post facto" and correlational research because the variables are not manipulated and rather by analysis we try to establish the cause - effect relationships and correlation of the variables X and Y. Two instruments were applied to the whole sample, to measure the variables: Efficiency level of direct purchases and for measure the variable level of control; which allowed us to collect information, relate and measure the study variables, make correlations and comparisons. The sample consisted of 81 people related to the Registration Zone No. XIII - Tacna Headquarters. The results obtained allowed us to establish that: The level of control has a significant impact on the efficiency of direct purchases in the Registration Zone No. XIII - Tacna Headquarters. 2016.